Statism, youth and civic imagination : a critical study of the National Youth Service Corps programme in Nigeria - Obadare, Ebenezer (Monograph series (Codesria), 2010)
This study explores the service-citizenship nexus in Nigeria, using the National Youth Service Corps (NYSC) programme as an empirical backdrop. It attempts to understand the relationship between civic service and citizenship on the one hand, and it examines the question as to whether youth service promotes a sense of citizenship and patriotism on the other. In the relevant studies on service and sociology, the assumption that service is antecedent to, and impacts positively on citizenship, is taken for granted. However, conclusions from this study call for an urgent rethinking of this wisdom. Using data from open-ended interviews, questionnaires and focus group discussions, the study traces the ways in which political dynamics in Nigeria have affected the implementation of the NYSC programme. The study articulates allegiance to national ideals as an essential foundation for creating and nurturing citizenship. Although it upholds the potential of national service as a tool for national integration, this research cautions against unalloyed faith in its presumed agency, arguing that the limitations imposed by the prevailing socio-political ecology should not be ignored.